2022
DOI: 10.1186/s13071-022-05251-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of preventive measures and serological screening tools for Leishmania infantum infection in dogs from Europe

Abstract: Background There are several screening tools for detecting Leishmania infantum infection in dogs and various preventive measures to protect against it. Some studies have investigated them, but not many have described their current use. The aim of this study was to investigate which preventive measures and serological screening tools for L. infantum infection were employed from 2012 to 2018 in dogs from different endemic European countries. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The biological activity and size of the sandfly population, as well as that of latent dogs contribute substantially to the dissemination of disease [ 17 ]. Regarding biological factors, individual factors, such as the use of bed nets and repellents were considered as influencing factors in several studies [ 18 20 ]. However, most studies failed to apply a theoretical and comprehensive framework to identify the specific factors that have the greatest impact on the transmission cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity and size of the sandfly population, as well as that of latent dogs contribute substantially to the dissemination of disease [ 17 ]. Regarding biological factors, individual factors, such as the use of bed nets and repellents were considered as influencing factors in several studies [ 18 20 ]. However, most studies failed to apply a theoretical and comprehensive framework to identify the specific factors that have the greatest impact on the transmission cycle.…”
Section: Introductionmentioning
confidence: 99%
“…This may be explained with the lack of compliance by owners when applying the preventive products on their dogs. In a recent study based on an online questionnaire sent to veterinary clinics in Europe analyzing strategies for preventing L. infantum infection or clinical disease in dogs, it was shown that repellents (86.2%), vaccination (39.8%) and Leishguard ® (15.3%) were the most frequently employed [46].…”
Section: Discussionmentioning
confidence: 99%
“…A field study showed its effectiveness in preventing clinical signs, reporting that it offered 68.4% and 92.7% vaccine protection [ 44 ]. However, CaniLeish ® has been off the market since 2021 [ 45 , 46 ]. The LetiFend ® (Laboratorios LETI, Barcelona, Spain) vaccine is a more recent vaccine, and unlike the others, it is the only commercial vaccine composed of a chimeric protein containing five antigenic fragments of four L. infantum proteins (histone H2A and ribosomal proteins LiP2a, LiP2b, and LiP0), with 72% efficiency [ 44 ].…”
Section: Introductionmentioning
confidence: 99%